2020
DOI: 10.4314/ijbcs.v13i7.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of proline content and antioxidant enzyme activities induced by drought stress in maize (<i>Zea mays L.</i>) by application of compost

Abstract: In sub-Saharan Africa, soil degradation and recurrent droughts are major obstacles to a sustainable agriculture. This study aimed at investigating the effect of compost addition to soil on proline content and activities of the antioxidant enzymes [catalase (CAT), ascorbate peroxidase (APX)] in maize plants, under drought stress conditions. The test was carried out in 20L plastic pots containing either sandy soil or sandy soil with the fertilizer, under natural conditions. The water deficit was induced at male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Cette contrainte constitue ainsi un problème majeur commun au Togo et au Bénin. C'est dans ce contexte que plusieurs travaux sont consacrés à la recherche de solutions durables dans la restauration, la fertilisation des sols cultivés au Togo (Toundou et al, 2014) mais aussi l'amélioration de la résistance au déficit hydrique (Bokobana et al, 2019). D'autres contraintes ont également été répertoriées lors de la présente étude.…”
Section: Discussionunclassified
“…Cette contrainte constitue ainsi un problème majeur commun au Togo et au Bénin. C'est dans ce contexte que plusieurs travaux sont consacrés à la recherche de solutions durables dans la restauration, la fertilisation des sols cultivés au Togo (Toundou et al, 2014) mais aussi l'amélioration de la résistance au déficit hydrique (Bokobana et al, 2019). D'autres contraintes ont également été répertoriées lors de la présente étude.…”
Section: Discussionunclassified
“…In organic farming, using leftover vegetables may increase soil fertility, which will enhance plant growth and nutritional value. For example, Bokobana et al [ 12 ] reported that the Comp treatment enhanced controllable maize growth and drought tolerance. Increasing the plant’s access to nutrients by using Comp can be further improved by adding plant growth-promoting microorganisms such as arbuscular mycorrhizal fungus (AMF).…”
Section: Introductionmentioning
confidence: 99%
“…Pour minimiser les impacts négatifs de la sécheresse sur la production agricole, plusieurs stratégies ont été développées. Il s'agit des pratiques culturales favorisant l'augmentation de la capacité de rétention d'eau du sol et/ou du développement du système racinaire des plants (semis sous couvert végétal, apport du compost, du fumier et/ou de l'engrais minéral) (Sissoko et al, 2013 ;Some et al, 2014 ;Bokobana et al, 2019 ;Sissoko et al, 2020). A ces pratiques nous pouvons ajouter les dates de semis, la densité de semis, l'application des régulateurs de croissance et l'utilisation de variétés tolérantes aux stress hydriques (Ouédraogo et al, 2010 ;Khan et al, 2018).…”
Section: Introductionunclassified